New larval trematodes in Biomphalaria species (Planorbidae) from Northeastern Argentina - Fernández, María Virginia (2016)
Larval trematodes infecting Biomphalaria tenagophila and B. occidentalis were surveyed in a suburban and semipermanent pond of Corrientes province, Northeastern Argentina. A total of 1,409 snails were examined between spring 2011 to winter 2013, and 8 different larval trematodes were studied morphologically. Three of these species–Echinocercaria sp. IV, Ribeiroia sp. and Echinocercaria sp. XIV–have been previously found in Corrientes province. Six other trematodes belonging to Strigeidae (Furcocercaria sp. III), Clinostomidae (Cercaria Clinostomidae sp.), Spirorchiidae (Cercaria Spirorchiidae sp.) and Echinostomatidae (Echinocercaria sp. 1, Echinocercaria sp. 2, Echinocercaria sp. 3) are new species parasitizing Biomphalaria snails. Cercaria Spirorchiidae sp. is the third larval trematode related to Spirorchiidae recorded in South America and the first one for Argentina. Cercaria Clinostomidae sp. is the first one related to Clinostomidae in northeastern Argentina. The prevalence of larval trematodes infecting B. tenagophila and B. occidentalis in the environment studied was low (˂5%) with the echinostome group better represented in terms of prevalence and species richness. Drought periods could affect the dynamics of parasitic transmission due to the absence of trematodes in the autumn and winter of the first seasonal cycle. However, in humid periods parasite transmission can occur throughout the year due to the presence of larvae in all seasons of the second seasonal cycle, although the less-warm seasons showed higher prevalence than the summer period probably related to the subtropical climate of Corrientes province.